Performance of DVB-T System under Multipath Fading with LS Channel Estimation and Equalization - Kavianirad, Shahrzad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Digital Video Broadcast-Terrestrial (DVB-T) is a broadly used digital television standard in use around the globe for terrestrial television transmission. It offers many services and enables efficient use of the available radio frequency spectrum than the previous multiplexing modulation techniques to provide high data rates along with robustness against multipath. However, due to the frequency selectivity of the channel, DVB-T systems show poor performance and high probability of errors. In this research, DVB-T system has been implemented in accordance with European Telecommunications Standards Institute (ETSI), EN 300 744 standard. Simulations and analysis based on performance evaluation of DVB-T system in Portable Indoor (PI), Portable Outdoor (PO), Rural Area (RA6), Rayleigh and Typical Urban (TU6) channel models has been conducted. In order to overcome the distortions caused by the multipath channel, Least Square (LS) channel estimation method has been proposed. BER performance of the system has been analysis for 4, 16 and 64 QAM constellations in all five channels. In order to clarify the results image transmission has been done for all three constellations in mentioned channels. As a result in received image distortion has been appeared as a salt and pepper noise, so that we proposed Median filter to overcome with channel noise. However in 4-QAM and 16-QAM the result was acceptable, in 64-QAM constellation result could not be clarify completely, although in RA6 channel with 24dB SNR and with usage of Median filter good improvement can be observed.

ÖZ: Sayısal Karasal Yayıncılık (SKY), karasal televizyon yayını için dünya çapında yaygın olarak kullanılan dijital televizyon standardıdır. Bu standart, çokyollu kanala karşı sağlamlığının yanında yüksek veri hızlarına ulaşmak için mevcut radyo frekans spektrumunun daha önceki modülasyon tekniklerinden daha etkili kullanımını sağlayan birçok hizmetleri sunmaktadır. Ancak, kanalın frekans seçici olduğu ortamlarda SKY sistemleri zayıf performans ve yüksek hata oranları vermektedir. Bu araştırmadaki benzetimler ETSI EN 300 744 standardına uygun olarak gerçekleştirilmiştir. SKY sisteminin performans değerlendirmesi için gerekli benzetim çalışmaları ve analizler Bina içi Taşınabilir (BT), Açık hava Taşınabilir (AT), Kırsal Alan (KA), Rayleigh ve Tipik Kentsel (TK) kanal ortamlarında gerçekleştirilmiştir. Çokyollu kanaldan kaynaklanan bozulmaların üstesinden gelebilmek için, En Küçük Kareler (EKK) kanal kestirim yöntemi önerilmiştir. Sistemin Bit Hata Oranı (BHO) 4, 16 ve 64 QAM kullanılarak beş farklı kanal durumunda analiz edilmiştir. Görüntü aktarımının söz konusu kanallar altında nasıl olacağını gösteren çalışmalar her üç işaret kümesi için gerçekleştirilmiştir. Alına görüntülerde tuz ve biber gürültü olarak bilinen bozulmalar ortaya çıkmış ve bu bozulmaların üstesinden gelebilmek için ortanca süzgeci önerilmiştir. 4 ve 16-QAM ortamlarında kabul edilebilir sonuçlar alınabilmesine rağmen 64-QAM kullanılması durumunda tatmin edici sonuçlar alınamamıştır ancak RA6 ortamında 24dB’de ortanca süzgeci kullanımıyla 64-QAM ortamında da iyileşme gözlemlenmiştir.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2015. Supervisor: Prof. Dr. Hasan Amca and Co-Supervisor: Assoc. Prof. Dr. Ahmet Rizaner .
Keywords: Electrical and Electronic Engineering; Digital television -Television broadcasting; Television broadcasting - Digital video; DVB-T; OFDM; LS estimation; multipath fading channels; median filter